Transformation of Environmental Education in Sennu-Sennureng Maccera Tappareng of Tempe Lake Wajo Regency: Sacred To Profane - Rapi, Muh. (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study aims to analyze immanent environmental education in sennu-sennureng maccera tappareng in this context is a reaffirmation of human commitment in preserving the environment. The method used in this field of research is qualitative research with a phenomenological paradigm. The interview and observation data were then analyzed by data reduction, data exposure, and conclusions/verification. Research findings show that senna-ensuring in the implementation of mascara apparent is loaded with environmental education as a form of symbolic communication built between communities inhabiting the shores of Tempe Lake Wajo Regency to maintain environmental sustainability, which in this case is divided into senna-ensuring mappalao baccara, senna-ensuring mannini pammali, and senna-ensuring mappable ise wanna. These sennu-sennureng are an inseparable part of transforming various sacred dimensions into profane. Something that was initially only the value of the relationship between man and the Creator developed into a relationship between man and man himself or the environment, which can be said to be a form of the transformative meaning of each stage in the mascara apparent procession. Immanent environmental education in sennu-sennureng maccera tappareng must continue to be preserved by continuing to actively transform sacred values into profane.